After American studies - Herlihy-Mera, Jeffrey, author.
1 online resource (x, 188 pages)
Keywords: "After American Studies is a timely critique of national and transnational approaches to community, and their forms of belonging and trans/patriotisms. Using reports in multicultural psychology and cultural neuroscience to interpret an array of cultural forms--including literature, art, film, advertising, search engines, urban planning, museum artifacts, visa policy, public education, and ostensibly non-state media--the argument fills a gap in contemporary criticism by a focus on what makes cultural canons symbolically effective (or not) for an individual exposed to them. The book makes important points about the limits of transnationalism as a paradigm, evidencing how such approaches often reiterate presumptive and essentialized notions of identity that function as new dimensions of exceptionalism. In response to the shortcomings in trans/national criticism, the final chapter initiates a theoretical consideration of a postgeographic and postcultural form of community (and of cultural analysis)."--Provided by publisher.